Analysis of Student Problem-Solving Ability Topics 3D Reviewed from Geometry Thinking Level - Ardiyanto, Bagas; Gunawan; Abdulloh, Maryam; Septiasari, Safrilia (Proceeding International Conference on Science and Engineering, 2020)
Each student has different problem-solving skills on the 3D topic. The study aims to find out the student problem-solving skills in the 3D Topics reviewed from geometry thinking level. This type of research is qualitative research with a case study approach. The subject in this study is as many as 20 subjects consisting of high problem-solving capabilities, moderate problem-solving capabilities, and low problem-solving capabilities. The data collection Instrument on this research is a level test of geometry thinking. The results showed that students in the category of high problem-solving skills were able to master level 0, Level 1, Level 2, and level 3 despite not being perfect, students in the category of problem-solving skills were able to master level 0, Level 1, and Level 2, students in the category of low problem-solving skills are only capable of mastering level 0 and Level 1.